How to prevent fire (safety measures and precautions) saving lives and properties in case of fire - Tadeo, Samuel C. (MMA Publications, 2005)
This book is developed to educate everyone on fire safety, prevention and control. Important pointers, reminders and valuable information disseminated by the Fire Department of Manila and Caloocan are also in this book to make sure that their message will be sent across to effect a meaningful reduction of the alarming fire losses, develop consciousness and involvement of all persons in the prevention and suppression of fires.